Turkish Physical Education Teachers' Use of Technology: Application and Diffusion of Technological Innovations - Ferman Konukman; Bijen Filiz (MDPI AG, 2024)
The purpose of this study was to determine Turkish physical education (PE) teachers' level of technological innovation use and attitudes regarding their applications and diffusion. This study consisted of 678 Turkish PE teachers. In total, 265 (39.1%) of the PE teachers were female, and 413 (60.9%) were male. A sequential explanatory mixed-methods design was used in this study. "The Applying and Diffusing Technological Innovations Scale for Teachers" was used for data collection. The results showed that the main obstacles the PE teachers face in using technological innovations were the cost of products; security and privacy problems; the need for new versions and technical support; the lack of time; the lack of interest; difficulty in accessing technology; and the lack of understanding. Moreover, there was a significant difference in the tendency to apply and diffuse technological innovations in terms of gender, school type, and school level. We found that the "ability to use innovations" sub-dimension affects the PE teachers' tendencies to apply and diffuse technology. As a result, we recommend providing various training programs on technological innovations to the older/longer-serving PE teachers, especially those working in public schools and secondary schools.